The effects of bracings on progressive collapse resistance of reinforced concrete multi-story frames - Miao, Lingyu (2017)
Terrorist attacks on famous iconic buildings in recent years, such as the explosion of Murrah Federal Building and 911 attacks on World Trade Center (WTC), have raised great concerns from the society and engineering community. The abnormal loading exerted by these attacks could damage individual load-carrying members, and consequently damage the whole structure by means of progressive collapse. In recent few decades, a range of research programs were launched to experimentally and analytically study the behaviours of structures under progressive collapse, as well as the load-carrying mechanisms to resist progressive collapse. Some remarkable programs include the in-situ tests done by Sasani (2008), laboratory tests and analytical studies done by Qian and Li from 2012 to 2016. However, most of the laboratory experiments focused on single-story reinforced concrete (RC) specimens, with no consideration of the strengthening effects of steel bracings. In this Final Year Project, experimental studies are carried out to study the effects of steel bracings on the resistance against progressive collapse. Three three-story reinforced concrete (RC) frames, with one bare frame and two frames strengthened by additional steel bracings are tested. The experimental results indicate that steel bracings can enhance the initial stiffness significantly, but the improvement on ultimate strength varies among different configurations of steel bracings. In addition, non-linear finite element modeling (FEM) is carried out to verify the reliability of analytical models. The analytical results show a general consistency with the experimental results.